2021
DOI: 10.1002/nano.202000271
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared responsive targeted drug delivery system that offer chemo‐photothermal therapy against bacterial infection

Abstract: To combat the rise of antibiotic resistant bacteria, it is essential to look upon other therapeutic solutions that do not solely depend upon conventional antibiotics. Here, we have designed a combinational therapeutic approach that kills bacteria with the conjunction of photothermal (PT) and antibiotic therapy. A near‐infrared (NIR) laser activated targeted drug delivery nano‐assembly delivers antibiotic as well as offer PT therapy (PTT). The synergistic application of both therapies increases the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Patel and co-authors developed a nanocomposite consisting of AuNRs coated with mesoporous silica. 218 This complex played a role of nanocarrier onto which the antituberculotic medicine, bedaquiline (BDQ), was loaded. The entire composite was wrapped in thermo-sensitive liposomes (TSLs) under the name GNR@MSNP@BDQ@TSL@NZX with NZX responsible for the bond between the nanocomposite and mycobacteria.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…Patel and co-authors developed a nanocomposite consisting of AuNRs coated with mesoporous silica. 218 This complex played a role of nanocarrier onto which the antituberculotic medicine, bedaquiline (BDQ), was loaded. The entire composite was wrapped in thermo-sensitive liposomes (TSLs) under the name GNR@MSNP@BDQ@TSL@NZX with NZX responsible for the bond between the nanocomposite and mycobacteria.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…These liposomes become permeable at a temperature of ∼50 °C, as previously shown. 17 To check the photothermal effect of IR 780, two different ratios of lipid/IR 780 (100:1 and 100:5 weight ratio) were prepared using a similar lipid film-based method. The resultant product, liposome-IR 780 (LI), was stored at 4 °C until further use.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The stability studies were carried out by following the protocol in our previously reported study. 17 Briefly, GM and [(GM@ Dox) LI]-PF solution were stored at 37 °C in cell culture media for 5 days. The nano-assemblies were monitored daily, and their stability was characterized by UV absorbance to track the longitudinal surface plasmon resonance (LSPR) intensity, aggregation index (AI), and zeta potential to monitor the change in surface charge.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental procedure of SAB formation was analyzed and systematically adapted for this purpose. [45][46][47] Correspondingly, the activation of carboxylate (R-COOH) presented on Ia, Ib and Ic (I series) to be covalently bound with primary amine (R-NH 2 ) was performed with application of amide coupling agents soluble in aqueous medium described in Section 4. [48][49][50][51] As a result, the dispersion of core-shell NMs was carried out as an eco-friendly process with different concentrations, which were determined experimen-tally by consecutive examination of SAB formation on Fourier transform IR (FT-IR).…”
Section: Functionalization Of Nps and Nrs And Respective Linking-reac...mentioning
confidence: 99%